Negative effects on the development of Chrysodeixis includens and Spodoptera cosmioides fed by peanut plants inoculated with entomopathogenic fungi - Vinha, Fernando Belezini; Rojas, Luis Angel Chicoma; Ramos Sales, Cinara; Monteiro Lima, Natalia Sarmanho; Nascimento, Joacir Do; De Carvalho, Lucas Amoroso Lopes; Lemos, Eliana Gertrudes De Macedo (Frontiers in Fungal Biology, 2023)
Recent studies have shown that entomopathogenic fungi, as endophytes, can have beneficial effects on plants, protecting them from defoliating insects. The potential of endophytic association by entomopathogenic fungi with the peanut crop has been little explored. In our study, we conducted experiments by inoculation of peanut seeds through a soil drench with nine strains/species of entomopathogenic fungi of the genera Metarhizium, Beauveria and Cordyceps before the transfer of two larval pests, Chrysodeixis includens and Spodoptera cosmioides. The parameters of larval growth rates, mortality, foliar consumption and larval period were determined. In addition, the endophytic capacity of these fungi in peanut plants and their persistence were investigated. In two replicate greenhouse trials for each larva, peanut plants were inoculated with fungi by the soil-drench method. We evaluated the performance of C. includens and S. cosmioides feeding on inoculated peanut plants starting at the 2nd larval instar. The larval and pupal weights of C. includens and S. cosmioides were significantly different among the fungal treatment groups, where insects feeding on control plants exhibited higher larval and pupal weights than insects feeding on treated plants. The differences in larval period showed that Control larvae pupated faster than the larvae fed on fungal-inoculated plants, fungal treatments had a larval period of 3 to 5 days more than the control. The mortality rates of C. includens and S. cosmioides were significantly different among the fungal treatment groups, where insects fed on control plants exhibited higher survival than insects fed on fungus-treated plants. The persistence of all Metarhizium fungi was higher in the soil compared to other fungi, and only the fungi Metarhizium and B. bassiana IBCB215 appeared in the phyllosphere of peanut plants. Although the fungus Cordyceps presented the worst performance among the fungal treatments, it presented significant differences from the control. Overall, our results demonstrate the negative effects of the fungi Metarhizium and B. bassiana on C. includens and S. cosmioides survivorship and development using whole peanut plant assays.